Dissolved organic carbon uptake in streams: A review and assessment of reach‐scale measurements. Issue 8 (28th August 2016) - Mineau, Madeleine M.; Wollheim, Wilfred M.; Buffam, Ishi; Findlay, Stuart E. G.; Hall, Robert O.; Hotchkiss, Erin R.; Koenig, Lauren E.; McDowell, William H.; Parr, Thomas B.
Abstract: Quantifying the role that freshwater ecosystems play in the global carbon cycle requires accurate measurement and scaling of dissolved organic carbon (DOC) removal in river networks. We reviewed reach‐scale measurements of DOC uptake from experimental additions of simple organic compounds or leachates to inform development of aquatic DOC models that operate at the river network, regional, or continental scale. Median DOC uptake velocity ( vf ) across all measurements was 2.28 mm min −1 . Measurements using simple compound additions resulted in faster vf (2.94 mm min −1 ) than additions of leachates (1.11 mm min −1 ). We also reviewed published data of DOC bioavailability for ambient stream water and leaf leachate DOC from laboratory experiments. We used these data to calculate and apply a correction factor to leaf leachate uptake velocity to estimate ambient stream water DOC uptake rates at the reach scale. Using this approach, we estimated a median ambient stream DOC vf of 0.26 mm min −1 . Applying these DOC vf values (0.26, 1.11, 2.28, and 2.94 mm min −1 ) in a river network inverse model in seven watersheds revealed that our estimated ambient DOC vf value is plausible at the network scale and 27 to 45% of DOC input was removed. Applying the median measured simple compound or leachate vf in whole river networks would require unjustifiably high terrestrial DOC inputs to match observed DOC concentrations at the basin mouth. To improve the understanding and importance of DOC uptake in fluvial systems, we recommend using a multiscale approach coupling laboratory assays, with reach‐scale measurements, and modeling. Key Points: Better understanding of DOC processing in river networks is needed Reach‐scale DOC uptake velocity is faster for simple compounds than leachates Reach‐scale DOC uptake velocities are implausibly fast at the network scale